Determinants influencing adoption of improved sericulture practices in Jammu (Current Horticulture, 2024)
main silk production districts are Anantnag, Kupwara,Pulwama, Baramula, Gandarbal, Udhampur, Rajouri,Kathua and Reasi. The gap between potential and actual yield obtained by silkworm rearers are not fully exploited. Keeping in view, socio-economic profile ofsilkworm rearers and deviations in adoption of recommended package of practices were identified to know the factors influencing same in three potential areas of Jammu province.